ECOLOGICAL STABILITY OF GRAIN CROP VARIETIES AND TASKS OF BREEDING - A. A. Goncharenko (Зерновое хозяйство России)
The article presents the results of the comparative study of the new and old varieties of six grain crops (winter rye, winter and spring wheat, winter triticale, spring barley, oats), conducted among the crops according to the range of environmental varying (CV), phenotypic stability (SF) and ecologic adaptability (bi) of productivity trait. The study shows that the new varieties of all crops excluding rye possess higher variability of productivity than the old varieties. The varieties with high potential of productivity the share of its variability, caused by environmental factors, increases, but the effect of variety gene type on the variability reduces. The conclusion has been made that if the potential productivity of the varieties increases, their environmental stability decreases and it can’t be raised with the breeding technologies. The breeding efficiency will be higher if its strategy is directed to the special adaptation of the varieties to the dominant conditions of the region. The priority should be given to the breeding of the varieties on the adaptability to the contrasting weather conditions. The ways of improvement of the breeding on the environmental stability are being discussed.